Evaluation the Propagation of Localized Corrosion Induced by Flow in Different Concentrations of Sodium Chloride and in the Presence of Corrosion Inhibitor - Gabriela P.C. Moreira; Bárbara L. Resende; Isabela A.F. Silva; Rhuan C. Souza; Luan C. Santos; José A.C.P. Gomes; Jefferson R. Oliveira; Guillermo Vilalta-Alonso; Alysson H.S. Bueno (Materials Research)
The growth of the oil and gas industry implies an understanding of corrosion and ways to mitigate pipeline failures. The objective of this research is to evaluate the propagation of localized corrosion induced by flow in different concentrations of sodium chloride and in the presence of corrosion inhibitor, associated with the wall shear stress. The API X65 steel specimens were drilled, with the purpose of simulating corrosion pits, and coupled to a modified ASTM G170 rotating cage.The experimental conditions were: (1) desaerated medium in the presence of CO2 under 5 bar, 120°C and concentrations of 0.1% or 10% sodium chloride; (2) aerated medium without CO2 at 40°C, without or with corrosion inhibitor. To evaluate the shear stress, Computational Fluid Dynamics (CFD) was used to understand the distribution on the surface of the samples. The results showed that the chloride concentration influenced the formation of the FeCO3 film and the corrosion rate. Furthermore, it was observed that the variation in diameter was more pronounced for the pits that had the smallest initial diameter, in all conditions evaluated. The highest values of diameter variation did not correspond to the highest values of shear stress imposed on each artificial pits.